Chromatin and Epigenetics 2020
DOI: 10.5772/intechopen.79975
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Circadian Rhythms: Bmal1 Gene Regulation

Abstract: Circadian rhythms that function in behaviour and physiology have adaptive significance for living organisms from bacteria to humans and reflect the presence of a biological clock. The engine of circadian rhythms is a transcription-translation feedback loop that is finetuned by epigenetic regulation in higher eukaryotes. We elucidated the chromatin structure of the Bmal1 gene, a critical component of the mammalian clock system, and have continued to investigate transcriptional regulation including DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 91 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Our results (Figure 2C and Figure 3A) showed that PER2 and Bmal1 did not show opposite oscillation patterns to each other, which is consistent with the previous report that peak times of the mRNA and protein expressions of the Per2 gene are different for 6−7 h. 28 The potential to modify circadian rhythms of 3βmWi-A is attractive in an era where commonplace 24 h lifestyles have led to an increased prevalence of circadian rhythm disorders. 29 Nontoxic technologies/ reagents with potential to manipulate the circadian period are desirable to avoid such disorders. However, the circadian clock is a robust system against stimuli other than light, and it cannot be easily modified by external factors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results (Figure 2C and Figure 3A) showed that PER2 and Bmal1 did not show opposite oscillation patterns to each other, which is consistent with the previous report that peak times of the mRNA and protein expressions of the Per2 gene are different for 6−7 h. 28 The potential to modify circadian rhythms of 3βmWi-A is attractive in an era where commonplace 24 h lifestyles have led to an increased prevalence of circadian rhythm disorders. 29 Nontoxic technologies/ reagents with potential to manipulate the circadian period are desirable to avoid such disorders. However, the circadian clock is a robust system against stimuli other than light, and it cannot be easily modified by external factors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Many chronic disorders including cancers and mood disorders are reported to link with circadian rhythm. 29 We can expect that some of these disorders are treated or prevented by this compound by manipulating RORa function.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation